Glucose Detection Devices and Methods Based on Metal–Organic Frameworks and Related Materials - Adeel, Muhammad; Asif, Kanwal; Rahman, Md. Mahbubur; Daniele, Salvatore; Canzonieri, Vincenzo; Rizzolio, Flavio (Advanced functional materials, 2021)
Assessment of glucose concentration is important in the diagnosis and treatment of diabetes. Since the introduction of enzymatic glucose biosensors, scientific and technological advances in nanomaterials have led to the development of new generations of glucose sensors. This field has witnessed major developments over the last decade, as the novel nanomaterials are capable of efficiently catalyzing glucose directly (i.e., act as artificial enzymes, therefore defined nanozymes) or to entrap enzymes that are able to oxidize glucose. Among other nanomaterials, metal–organic frameworks (MOFs) have recently provided a tremendous basis to construct glucose sensing devices. MOFs are large porous crystalline compounds with versatile structural and tuneable chemical properties. In addition, they possess catalytic, peroxidase‐like, and electrochemical redox activity. This review comprehensively summarizes the general characteristics of MOFs, their subtypes, and MOF composites, as well as MOF‐derived materials employed to construct electrochemical, optical, transistor, and microfluidic devices for the detection of glucose. They include enzymatic, nonenzymatic, wearable, and flexible sensing devices and methods. The review also outlines the design and synthesis of MOFs and the working principles of the different transduction‐based glucose sensors and highlights the current challenges and future perspectives. The use of metal–organic frameworks (MOFs) for the construction of various types of glucose sensors is summarized. Enzymatic, nonenzymatic, wearable, and flexible sensing devices and methods are considered. The synthesis of MOFs, the working principles of the different transduction‐based glucose sensors, current challenges and future perspectives of MOFs and their related materials‐based‐glucose sensors are also highlighted.